2012
DOI: 10.3329/bjch.v35i2.10355
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antinuclear Antibody in Childhood Rheumatic Diseases by Immunofluorescence Assay and Enzyme Immuno Assay

Abstract: Background: Anti-nuclear antibodies (ANAs) are specific antibodies directed against a variety of nuclear antigens. Indirect immunofluorecence (ANA-IFA) and Enzyme Immunoassay (ANA-EIA) are commonly used methods for ANA detection. The positivity of ANA-IFA using HEp-2 cell substrate is 90-100% in systemic rheumatic diseases. On the other hand positivity of ANA-EIA is found to be much lower in different studies. In Bangladesh most of the laboratories use ANA-EIA method.Objectives: To detect ANA by Immunofluorece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Regarding autoantibody profiles, ANA was positive among all the patients (100%), and results of other studies such as those by Dipti et al and Weiss, who found 100% and 99% ANA positivity, respectively, 29 , 30 matched with our results, but ANA (IIF) was positive in 94% of SLE patients in the study by Gomes et al 19 Meanwhile, anti-dsDNA was detected in 83% of the samples in our study. Sahin et al found a similar result (84.8%), 24 but a lower percentage was reported by Balci et al (45.3%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding autoantibody profiles, ANA was positive among all the patients (100%), and results of other studies such as those by Dipti et al and Weiss, who found 100% and 99% ANA positivity, respectively, 29 , 30 matched with our results, but ANA (IIF) was positive in 94% of SLE patients in the study by Gomes et al 19 Meanwhile, anti-dsDNA was detected in 83% of the samples in our study. Sahin et al found a similar result (84.8%), 24 but a lower percentage was reported by Balci et al (45.3%).…”
Section: Discussionsupporting
confidence: 90%
“…Variable results were obtained from different studies; Balci et al found that anti-CL IgG and IgM were positivity seen in 8 (15.1%) and 11 (20.8%) patients, respectively, 17 while Hiraki et al and Kim et al found that antiphospholipid antibodies were present in 32% and 42.8% of patients, respectively. 25,28 Regarding autoantibody profiles, ANA was positive among all the patients (100%), and results of other studies such as those by Dipti et al and Weiss, who found 100% and 99% ANA positivity, respectively, 29,30 matched with our results, but ANA (IIF) was positive in 94% of SLE patients in the study by Gomes et al 19 Meanwhile, anti-dsDNA was detected in 83% of the samples in our study. Sahin et al found a similar result (84.8%), 24 but a lower percentage was reported by Balci et al (45.3%).…”
Section: Discussionsupporting
confidence: 89%
“…In this study ANA (IIF) was present in 94% SLE patients where Dipti et al [19] and Weiss [20] found 100% and 99% ANA positivity by IIF method respectively in their study. Homogenous pattern of ANA was found as the predominant (54%), followed by fine speckled (18%) and coarse speckled (14%) pattern in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…Autoimmune diseases are conditions in which the immune system damages specific organs or tissues and are characterized by the presence of antinuclear antibodies (ANA) in the blood of the patients. ANA are specific antibodies directed against a variety of nuclear antigens which have the capability of binding and destroying certain structures within the nucleus of the cells and are detected in the serum of the patients with rheumatic & non rheumatic diseases [1]. Although lower amounts of these antibodies are seen in normal individuals, an increase in titres are exclusively seen in patients with autoimmune diseases and serve as markers for diagnosis and prognosis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although lower amounts of these antibodies are seen in normal individuals, an increase in titres are exclusively seen in patients with autoimmune diseases and serve as markers for diagnosis and prognosis [2]. These antibodies are involved not only in disease pathogenesis but also constitute basis for diagnosis and treatment [1]. Their detection with high sensitivity and specificity is therefore of utmost importance.…”
Section: Introductionmentioning
confidence: 99%